Meibomian Gland Morphology Changes After Cataract Surgery: A Contra-Lateral Eye Study - Chang, Pingjun; Qian, Shuyi; Xu, Zhizi; Huang, Feng; Zhao, Yinying; Li, Zhangliang; Zhao, Yun-e (Frontiers in Medicine, 2021)
Purpose: To evaluate the morphology changes of meibomian gland (MGs) after cataract surgery. Setting: Hangzhou Branch of the Eye Hospital of Wenzhou Medical University, Zhejiang, China. Methods: In this contra-lateral eye study, 40 patients received unilateral cataract surgery for age-related cataract. All patients underwent the evaluation of non-invasive break-up time (NIBUT) and lower tear meniscus height (TMH) before the surgery and 6 months postoperatively. The MGs were evaluated via image J and Meibomian Gland Bio-image Analyzer. MG dropout, length, width, area, gland diameter deformation index (DI), and gland signal index (SI) were recorded. Results: MG length, width, area, DI, and SI were significantly decreased after cataract surgery in the study group (operated eyes, P < 0.001, P = 0.003, P < 0.001, P = 0.001, and P < 0.001, respectively) and showed no significant changes in the control group (non-operated eyes) (all P > 0.05). MG loss increased more in the study group (P = 0.030), and the changes in TMH and NIBUT were not significantly different between the two eyes (both P > 0.05). Conclusion: Cataract surgery aggravated meibomian gland morphology, such as MG loss, MG length, width, area and SI, and produced no change in NIBUT and TMH at 6 months postoperatively.